2010
DOI: 10.1111/j.1743-6109.2010.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Copulatory Pattern of Male Rats in a Multiple Partner Choice Arena

Abstract: Introduction It has been demonstrated that testing conditions may influence sexual performance in many mammals, including male rats. We recently developed a multiple partner choice arena (MPCA) consisting of four acrylic cylinders placed in a cross pattern with one male in each cylinder. A sexually receptive female rat was introduced into the center of the MPCA and was allowed to choose a male to copulate with. The female showed a preference for one of the four males, remaining longer and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Another example of this phenomenon is seen in more "natural settings", in which female rats determine the pace of mating in a multiple choice arena. The non-preferred males in these tests are less often visited by the females, resulting in longer intercopulatory intervals, and become more efficient (more mounts result in intromissions), resulting in shorter ejaculation latencies than when they are tested in a situation where they can pace the mating themselves [20]. The efficiency of the rat is thus reflected in the intromission ratio.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Another example of this phenomenon is seen in more "natural settings", in which female rats determine the pace of mating in a multiple choice arena. The non-preferred males in these tests are less often visited by the females, resulting in longer intercopulatory intervals, and become more efficient (more mounts result in intromissions), resulting in shorter ejaculation latencies than when they are tested in a situation where they can pace the mating themselves [20]. The efficiency of the rat is thus reflected in the intromission ratio.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Nevertheless, although we were able to demonstrate in a previous study that male rats ejaculate sooner when they compete for a stimulus female in the MPCA [26], there are few studies in which two or more males have been simultaneously paired with a receptive female to analyze the effect this has on the speed of ejaculation. There is some evidence suggesting that certain stressinducing tactile stimuli, such as electric shocks to the paw or tail pinches, are capable of stimulating ejaculation in male rats [13,26,[28][29][30]. However, some researchers have suggested that this facilitatory effect is mediated by the activation of the dopaminergic system instead the serotonergic system [30].…”
Section: Methodsmentioning
confidence: 56%
“…However, in the subsequent ejaculatory series, these parameters begin to increase progressively until the male reaches its sexual satiety. Compared with rats in the SA, we can demonstrate that the male rat tested in the MPCA reaches his first ejaculation earlier (a mean of 100 seconds of ejaculatory latency and 4.7 intromissions), showing similar signs to those presented in the PE in men [26], although this criterion has not yet been established in male rats. These results suggest that if the MPCA satisfies the three criteria proposed by Willner, this arena may be more suitable for studying PE than the current animal model.…”
Section: Introductionmentioning
confidence: 54%
“…Such sexual imprinting has been extensively documented in birds [13] as well as in some mammal species [14,15]. Although later experiences can influence sexual behavior [16], imprinted preferences often dominate [13,15]. In humans, sexual imprinting has been suggested to contribute to the development of both common and rare preferences, including intercultural diversity in sexual practices [17–19] and paraphilias [20–22].…”
Section: Introductionmentioning
confidence: 99%